PENGARUH PEMBERIAN LATIHAN ABDOMINAL STRETCHING TERHADAP PENURUNAN INTENSITAS NYERI HAID (DISMINORE) PADA REMAJA PUTRI STIKES MADANI YOGYAKARTA - Arif Tirtana; Maulida Rahmawati Emha; Amilia Azma (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2018)
Dysmenorhea is the most common gynecological problem during adolescence period. Menstrual cramps (dysmenorhea) is felt by women on the first day of their menstruation. Abdominal Stretching exercise is a muscle stretching exercise, especially on the abdomen that is designed to increase muscle strength and muscle flexibility. Therefore, it is expected to reduce menstrual cramps in women. To evaluate the effect of Abdominal stretching exercise on the level of menstrual cramps (dysmenorhea) level in STIKes Madani Yogyakarta student. This research is quantitative research with experimental research design. The design of this research is quasy experiment used pretest- posttest with control group. The subjects were recruited using purposive sampling technique. The results showed that before doing abdominal exercise streatching mostly (66.7%) experienced moderate pain intensity and after treatment of reduced intensity pain (60%). The statistical test using Wilcoxon test obtained p value 0,000 (